Long-term outcome of cyclosporin rescue therapy in acute, steroid-refractory severe ulcerative colitis - Molnár, Tamás (SAGE Publications, 2014)
BACKGROUND: Although cyclosporin is effective in severe ulcerative colitis (UC), long-term colectomy rate varies between 60 and 88% among patients in whom cyclosporin initially induced remission. The aim of our study was to evaluate the long-term outcome and the optimal duration of cyclosporin therapy in acute, severe UC. METHODS: A total of 73 patients underwent i.v. cyclosporin therapy for a steroid refractory flare up of UC between 1998 and 2009. All patients were treated with 1 mg/kg i.v. methylprednisolone for 3–7 days before the administration of cyclosporin. Patients received i.v. cyclosporin of 4–5 mg/kg for 5 days following oral treatment. RESULTS: The mean follow up after the initiation of cyclosporin was 4.2 years. There were 20 patients who underwent early colectomy. Cyclosporin had to be discontinued due to side effects in 22 patients. Cyclosporin failed and late colectomy was performed in 14 of the 53 responders. Duration of cyclosporin treatment was significantly longer in those who avoided colectomy. The probability of avoiding colectomy proved to be 66% in case of 1-year treatment period with cyclosporin. The longer treatment period resulted in longer colectomy-free disease course. CONCLUSIONS: Cyclosporin is effective in acute, severe UC during long-term follow up. Our data suggest that the longer cyclosporin is used, the more it is possible to avoid colectomy in the future.